Alantolactone Enhances the Phagocytic Properties of Human Macrophages and Modulates Their Proinflammatory Functions - Barbara Gierlikowska; Wojciech Gierlikowski; Urszula Demkow (Frontiers Media S.A., 2020)
Aim of the StudyPhagocytosis is a crucial element of innate immune defense involved in bacterial killing. The aim of our study was to evaluate the influence of alantolactone on phagocytosis and cytokines release by THP1-derived macrophages. We assessed whether antimicrobial compound alantolactone (a sesquiterpene lactone present in Inula helenium L.) is able to stimulate immune functions of macrophages by increase of S. aureus uptake, phagosome acidification and further stimulation of phago-lysosomes formation. Simultaneously, we tested influence of alantolactone on cytokines/chemokines production and p65 NF-κB concentration. The activity of alantolactone was compared with clarithromycin at concentration 20 µM.MethodsThe cytotoxicity of alantolactone as well as S. aureus uptake, pH of phagosomes and phago-lysosomes fusion were analysed with flow cytometry. Reactive oxygen species and superoxide production were evaluated spectrophotometrically. The efficiency of phagocytosis was evaluated via quantifying viable bacteria (CFU). The effect on p65 protein concentration and cytokine production by macrophages were measured by enzyme-linked immunosorbent assay (ELISA).ResultsAlantolactone enhanced phagocytosis via increase of S. aureus uptake, acidification of phagosomes, and later stimulation of phago-lysosomes fusion. Alantolactone treatment resulted in ROS and superoxide production decrease. Furthermore, alantolactone inhibited production of pro-inflammatory cytokines TNF-α, IL-1β, IL-6, and IL-8 as well as decreased p65 concentration, the subunit responsible for NF-κB activation and cytokine production and simultaneously stimulated release of anti-inflammatory mediators (IL-10 and TGF-β).ConclusionResults of our study indicate that alantolactone enhances clearance of S. aureus, and simultaneously modulates immune response, preventing collateral damage of the surrounding tissues. Considering the importance of phagocytosis in the pathogen killing, alantolactone may have a great potential as the supportive treatment of S. aureus infections. Further in vivo studies are warranted to confirm this hypothesis.